Association between atrial fibrillation and cardiac implantable defibrillator detected heart failure status. (19th May 2022) - Vitali, F; Tavoletta, V; Giano, A; Calo, L; Santini, L; Savarese, G; Dello Russo, A; Santobuono, VE; Mattera, A; Lavalle, C; Amellone, C; Pecora, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In heart failure (HF) patients, atrial fibrillation (AF) is a common comorbidity and is associated with a worse prognosis. Implantable defibrillator (ICD) diagnostics allow continuous monitoring of atrial high-rate events (AHRE), as a surrogate of AF, and are equipped with algorithms for HF monitoring. We evaluated the association between the values of the multisensor HF HeartLogic Index and the incidence of AF, and assessed the performance of the Index in detecting follow-up periods of significantly increased AF risk. Methods: The HeartLogic feature was activated in 568 ICD patients. The median follow-up was 25 months [25th–75th percentile: 15-35]. The HeartLogic algorithm calculates a daily HF index and identifies periods IN the alert state on the basis of a configurable threshold. The endpoints were: daily AF burden of ≥5 minutes, ≥6 hours and ≥23 hours. Results: The HeartLogic index crossed the threshold value 1200 times (0.71 alerts/patient-year). The time IN the alert state was 13% of the total observation period. During the observation period, an AF burden of ≥5 minutes/day was documented in 183 (32%) patients, ≥6 hours/day in 118 (21%) patients, and ≥23 hours/day in 89 (16%). On using a time-dependent Cox model, the weekly time IN the alert state was independently associated with an AF burden of ≥5 minutes/day (HR:1.95, 95%CI:1.22-3.13, p=0.005), ≥6 hours/day (HR:2.66, 95%CI:1.60-4.44, p<0.001), and ≥23 hours/day (HR:3.32, 95%CI:1.83-6.02, p<0.001), after correction for baseline confounders. Comparison of the episode rates in the IN-alert state with those in the OUT-of-alert state yielded HRs ranging from 1.57 to 3.11 for AF burden from ≥5 minutes to ≥23 hours. Conclusions: The HeartLogic alert state was independently associated with AF occurrence. The intervals of time defined by the algorithm as periods of increased risk of HF allow risk stratification of AF according to various thresholds of daily burden.